2016
DOI: 10.1016/j.jpainsymman.2016.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Racial Differences in Stress, Coping, and Health-Related Quality of Life in Chronic Kidney Disease

Abstract: Objective Health-related quality of life (HRQOL) is an important outcome for patients living with chronic kidney disease (CKD), and it is necessary to better understand potential gender and racial differences as well as predictors associated with reduced HRQOL so effective interventions can be developed. Methods Participants included 182 patients with CKD who were administered a battery of questions that included the Medical Outcomes Study-Short Form 36; Perceived Stress Scale, and the Brief COPE. Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 22 publications
1
29
1
4
Order By: Relevance
“…(55) Moreover, both racial and gender differences in coping with psychosocial stress, including discrimination, are important to consider, as they were detected in various non-CKD samples, and coping strategies have been noted to vary among men and women with CKD, with women showing a broader range of strategies that can buffer the effects of stress. (56)…”
Section: Discussionmentioning
confidence: 99%
“…(55) Moreover, both racial and gender differences in coping with psychosocial stress, including discrimination, are important to consider, as they were detected in various non-CKD samples, and coping strategies have been noted to vary among men and women with CKD, with women showing a broader range of strategies that can buffer the effects of stress. (56)…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gemmell et al. evaluated 151 dialysis patients and found that the wider range of coping strategies used by women may be associated with buffering the link between perceived stress and quality of life . In another study, Saracho‐Rotaeche found avoidance and adaptive mechanisms are coping strategies that influence the psychological well‐being of dialysis patients…”
Section: Introductionmentioning
confidence: 99%
“…This result is in line with studies by Saad et al and Gemmell et al In both of these studies, the investigators found no significant difference in QOL scores between males and females. 6,25 Nevertheless, several studies have reported a significant influence of gender on QOL. Sayin et al documented males to have worse QOL than females, whereas Valderrábano et al reported the opposite.…”
mentioning
confidence: 99%